(untitled) (Research, Society and Development, 2021)
This is a systematic review of the literature in order to present scientific evidence about the best therapy for anal fissure. Retrospective and analytical study carried out from 1989 to 2020, in the Bireme, Pubmed and Scielo databases. The association of the descriptors “anal fissure” was used; "Aloe"; “Clinical treatment”; "vitamin A"; “Coloproctology”. Of the 238 articles analyzed, 38 were included in the review for meeting the inclusion criteria. Among the results, it was shown that conventional treatments, despite being effective (the gold standard being internal lateral sphincterectomy), have relevant side effects, thus, it is concluded that further research will be necessary to prove the effectiveness of new treatment options.